Challenges and trends of recognition of accountants’ competences - Budrienė, Liucija; Kvekšienė, Milda; Meškelienė, Audronė (Buhalterinės apskaitos teorija ir praktika, 2014)
Accountants’ competences are differently defined by employers, representatives of professional organizations and accountants themselves. The aim of the research is to study the accountant's competences and their recognition after they have been gained during non-formal and informal learning. The article deals with the concept of competence. It was found out from the studies of theoretical sources that knowledge comprises the basis of competence and skills, as the most important criteria of the employee’s professionalism, come with experience. Competence as a tested skill is a necessary condition of competency, though. Personal skills are being developed and perfected following competences defined in profession standards according to labour market needs. Changes lead to urge of accounting professionals to acquire new competences and formalize them. There was carried out empirical study on accountant's professional competences. In order to carry out empirical study there was selected an employers’ questionnaire based on a method of a structured questionnaire, there also was performed an analysis of job advertisements. When the results of study were summarized, six accountant‘s professional competences were framed. They were related with subjects of KSC Accounting study program and results of the studies in order to determine what subjects of the candidates could be accepted, after their competences, acquired during non-formal and informal learning, had been recognized. Recognition of competences, acquired in the non-formal way of learning, leads a person to professional growth and allows to pursue a professional career, promotes self-knowledge, offers opportunities to gain formal qualifications at lower costs.
Keywords: competence; qualification; recognition of non-formal competences; non-formal and informal learning